Pemberdayaan Masyarakat “PEMERIKSAAN KESEHATAN MANDIRI” di Perum Cipta Graha Mandiri Rw 11 Kelurahan Sukarindik - Bella Wahyu Puspita; Alifa Kanasya Sukasah; Olive Makhira Darlianto; Nawal Nur Ramadhani; Fitria Pancara Gunawati; Sofy Nur Ismi Alfatah; Andy Muharry (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2024)
The results of the 2018 Riskesdas show an increase in the prevalence of non-communicable diseases (NCDs) compared to 2013 data, such as cancer, stroke, chronic kidney disease, diabetes mellitus, and hypertension. The prevalence of diabetes mellitus increased from 6.9% to 8.5%, while hypertension increased from 25.8% to 34.1% based on blood sugar and blood pressure examinations. In this context, community empowerment is very important to increase awareness of the importance of routine health checks and early detection of NCDs. One strategic effort is the establishment of Posbindu in each region to facilitate public health checks. However, several regions, including Cipta Graha Mandiri Housing in Tasikmalaya City, do not yet have Posbindu due to low community participation in routine health checks and limited procurement of Posbindu by the Health Center. This condition risks making people unaware of their health problems, which can cause serious complications and reduce quality of life. Through this empowerment program, it is hoped that the community will be more active in maintaining their health, carrying out early detection of NCDs, and increasing awareness of the importance of a healthy lifestyle.